Development of SIAIR Interactive Media Assisted with Songs to Improve Learning Outcomes on Water Cycle Material in Elementary School - Rahayu, Yulina Sri; Sutikno, Putri Yanuarita (Jurnal Pijar Mipa, 2025)
Students' understanding of the water cycle material is still relatively low, which is caused by the limited learning media used. This has an impact on the low learning outcomes of students. This study aims to develop interactive media SIAIR assisted by songs to improve student learning outcomes on water cycle material. The novelty of this media lies in the integration of songs with various interactive digital media components, such as text, animated videos, simulation games, and digital comics, which are adapted to the thinking ability of elementary school students. This research uses the R&D method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of 41 fifth-grade elementary school students. Data collection techniques through test techniques in the form of pretests and posttests, as well as non-test techniques in the form of observation, interviews, documentation, and questionnaires. The data obtained were then analyzed through product assessment, normality test, paired samples t-test, and N-Gain test. The results showed that the song-assisted SIAIR interactive media was very feasible, with a score of 93% from media experts and 94% from material experts. This media is also considered practical by students and teachers, with a practicality level of 97.78% from small groups, 96.56% from large groups, and 100% from teachers. In addition, the effectiveness of the media in improving learning outcomes has been proven empirically. Based on the paired samples t-test, the small group showed a significance value (2-tailed) of 0.001 and N-Gain of 0.5398 with a moderate category. Then, the large group obtained a significance value (2-tailed) of 0.000 and N-Gain of 0.5617 with a moderate category. Based on the results of this study, it can be concluded that SIAIR interactive media assisted by songs is a feasible, practical, and effective learning innovation to improve student learning outcomes on water cycle material.